Problem-based learning in Master of Public Policy Programme - Sanusi, Junedah; Alhabshi, Sharifah Mariam; Shahier, Nur Ain; Tahir, Rohayatimah Muhammad; Md Khalid, Khadijah (2017)
To train students to think critically and innovatively and to apply their knowledge in different settings, the Malaysian Education Blueprint was developed. One of the best approach to shifting students focus to higher-order thinking skills is the use of real Problem-Based Learning (PBL) techniques. To support development of students' competencies for problem solving, group work and self-management, PBL has previously been used to bring significant positive impact across some target postgraduate students in Master of Business Administration programme in terms of educational gains. No study has been done so far on the implementation of PBL or other approaches of student/peer-centred learning in a Master of Public Policy (MPP) programme. This study therefore, aims to examine the impact of PBL pedagogy applied to some selected Public Policy courses of the MPP programme in INPUMA, University of Malaya, on students' learning effectiveness and perception. This study adopts quantitative and qualitative designs using closed-ended (on a Likert-type scale) and openended questionnaires for onward analysis with the aid of SPSS and Nvivo softwares respectively. The results from the study would support using PBL in teaching Public Policy courses to improve students' learning outcomes as well as creating both competent and experienced postgraduate students having learning growth significantly higher than students who pass through the passive and conventional lecturer-centered learning approach. Besides adding to the empirical literature on PBL application to Public Policy education, this study would push postgraduate students to develop their soft skills and train their judgment in evaluating the accuracy of shared information and to offering specific suggestions that can be of importance to future researchers. Furthermore, the perceptions of student on PBL through peer feedback would allow identification of strengths and weaknesses of PBL in the light of PBL implementation, thereby, meeting with the Malaysian Education Blueprint and goals.